Sie sind auf Seite 1von 4

Kuta Software - Infinite Algebra 1

Name

Graphing Lines

Sketch the graph of each line.

1

1) y = − 5 x − 2 6 4 2 −6 −5 −4 −3
1)
y = − 5 x − 2
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
5
3)
y = −
2 x
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
5)
y = 2 x − 5
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
Date Period 2) y = −5 x − 1 6 4 2 −6 −5 −4
Date
Period
2)
y = −5 x − 1
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
4)
y = −7 x + 3
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
6)
y = −6 x + 1
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6

-1-

1

7) y = − 3 x + 4 6 4 2 −6 −5 −4 −3
7)
y = − 3 x + 4
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
9)
y = − 2
5 x − 4
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
11)
y = −6 x + 5
6
4
2
−6 −5
−4 −3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
8) y = 0 6 4 2 −6 −5 −4 −3 −2 −1 0 1
8)
y = 0
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
10)
y = 7 x − 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6
12)
y = − 5 2 x + 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1 2
3
4
5
6
−2
−4
−6

-2-

Kuta Software - Infinite Algebra 1

Name

Graphing Lines

Sketch the graph of each line.

1) y = − 1 5 x − 2 6 4 2 −6 −5 −4
1)
y = − 1
5 x − 2
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
5 3) y = − 2 x 6 4 2 −6 −5 −4 −3 −2
5
3)
y = −
2 x
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
5) y = 2 x − 5 6 4 2 −6 −5 −4 −3 −2
5)
y = 2 x − 5
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
Date Period 2) y = −5 x − 1 6 4 2 −6 −5 −4
Date
Period
2)
y = −5 x − 1
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
4)
y = −7 x + 3
6 4 2 −6 −5 −4 −3 −2 −1 0 1 2 3 4 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
6)
y = −6 x + 1
6 4 2 −6 −5 −4 −3 −2 −1 0 1 2 3 4 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
-1-
7) y = − 1 3 x + 4 6 4 2 −6 −5 −4
7)
y = − 1
3 x + 4
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
9)
y = − 2 x − 4
5
6 4 2 −6 −5 −4 −3 −2 −1 0 1 2 3 4 5
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
11) y = −6 x + 5 6 4 2 −6 −5 −4 −3 −2
11)
y = −6 x + 5
6
4
2
−6 −5
−4 −3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
8) y = 0 6 4 2 −6 −5 −4 −3 −2 −1 0 1
8)
y = 0
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
10)
y = 7 x − 5
6 4 2 −6 −5 −4 −3 −2 −1 0 1 2 3 4 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6
12) y = − 5 2 x + 5 6 4 2 −6 −5 −4
12)
y = − 5 2 x + 5
6
4
2
−6
−5
−4
−3
−2
−1 0
1
2
3
4
5
6
−2
−4
−6

-2-